Advances in the management of intraocular foreign bodies - Ohlhausen, Marc; Menke, Bryant A.; Begley, Jack; Kim, Sean; Debiec, Matthew R.; Conrady, Christopher D.; Yeh, Steven; Justin, Grant A. (Frontiers in Ophthalmology, 2024)
Intraocular foreign bodies (IOFBs) remain a severe complication of ocular trauma commonly encountered worldwide. This literature review aimed to discuss current practice patterns, areas of controversy, and advances in the management of IOFBs. Injuries involving IOFBs carry significant ocular morbidity and management can be extremely challenging. A systematic approach to preoperative evaluation and IOFB surgical management is detailed in this article and should be applied in each case. The location and composition of an IOFB have important implications on surgical approach and timing, especially in cases of toxic metals and vegetable matter. The advantages, disadvantages, and previous literature regarding immediate versus delayed foreign body removal are presented. Surgical approaches are described, with an emphasis on posterior chamber IOFB management and removal via pars plana vitrectomy. Final visual acuity is variable, but approaches have been used to prognosticate outcomes including the Ocular Trauma Score. By synthesizing current IOFB literature, the goal is to provide practitioners with guidance that will maximize the chances of surgical success and patient outcomes.